Aeromagnetic signatures reveal a back-arc basin imposed upon the inherited rifted margin of the East Antarctic craton - ARMADILLO, EGIDIO; BOZZO, EMANUELE; Ferraccioli F.; Jordan T. A. (2009)
The Wilkes Subglacial Basin (WSB) represents a largely unexplored, approximately 1400 km-long and up to 600 km-wide subglacial depression, buried beneath the over 3 km-thick East Antarctic Ice Sheet. During the 2005-06 austral summer an extensive aerogeophysical survey was flown to investigate the WSB adjacent to northern Victoria Land (NVL), and included the acquisition of new airborne radar, aeromagnetic and aerogravity data. Several contrasting models for the origin of the basin have been previously proposed, and are based primarily on relatively sparse gravity data. These range from Cenozoic flexure, to distributed crustal extension of unknown age (possibly Mesozoic to Cenozoic), and even compression along the margin of craton. Our recent aeromagnetic data reveal that the basin is structurally controlled and has a tectonic origin, at least adjacent to NVL. The eastern margin of the basin is imposed upon an Early Paleozoic thrust fault belt, which can be traced under the ice using aeromagnetic signatures from exposures in Oates Land and the Ross Sea coast. Aeromagnetic patterns reveal that the western margin of the basin is imposed upon a Proterozoic-age shear zone mapped in the Mertz Glacier, and that is interpreted from geological studies to represent the continuation of a coeval shear zone in Australia. The broad aeromagnetic and satellite magnetic low over the WSB contrasts with the high over the un-reworked Proterozoic craton to the west of the basin, and is interpreted to reflect Neoproterozoic-age sediments deposited along the rifted margin of the craton. Magnetic intrusions within the WSB are interpreted as back-arc plutons that formed later in response to Cambrian-Ordovician age subduction along the paleo-Pacific margin of Gondwana. The aeromagnetic interpretation for a former broad back-arc basin in the WSB is supported by the occurrence of low-grade metasedimentary rocks of back-arc affinity in Oates Land, and also by the similarity in long-wavelength magnetic anomaly signatures of the WSB and the ...